(untitled) (Research, Society and Development, 2022)
Objectives: Analyze the repercussions of pregnancy in pregnant adolescents discussing mental disorders and difficulties in performing prenatal care in a reference hospital in Pernambuco. Methods: Descriptive, exploratory, cross-sectional study with quantitative and qualitative method. We used a semi-structured script for the interview and questionnaire prepared by the authors and the Self-Reporting Questionnaire (SRQ-20) with a sample of 32 pregnant adolescents. The quantitative data were analyzed with the aid of epi-info software using the measures of central tendency and their dispersions and qualitative, analyzed according to Minayo. The study was approved by the Ethics Committee in Research under opinion 4.310.337 and followed all ethical precepts from the National Research Ethics Commission (CONEP) Resolution 510/16. Results: The importance of the desire for pregnancy, family, and partner support for the psychological and emotional repercussions of the pregnant woman was evidenced. It was found through the SRQ-20 a possible mental suffering of the participants, with 68.75% (n=22). The main difficulties met in prenatal care: waiting and care time, and lack of humanized care. Conclusions: Teenage pregnancy is experienced in a variable way, including emotional aspects of happiness and sadness, which vary according to the adolescent’s acceptance of pregnancy, family and partner support, body satisfaction and perspectives for the future.